Efficient and Stable Inverted Planar Perovskite Solar Cells Using a Triphenylamine Hole‐Transporting Material. Issue 9 (19th April 2018) - Chen, Rui; Bu, Tongle; Li, Jing; Li, Wei; Zhou, Peng; Liu, Xueping; Ku, Zhiliang; Zhong, Jie; Peng, Yong; Huang, Fuzhi; Cheng, Yi‐Bing; Fu, Zhengyi
Abstract: Inverted perovskite solar cells (PSCs) with a p‐i‐n structure have attracted great attention. Normally, inorganic p‐type metal oxides or polymers are used as the hole‐transport material (HTM), a vital component in the inverted PSCs. However, this type of HTM often requires high processing temperatures and/or high costs. On the other hand, a commonly used organic HTM, poly(3, 4‐ethylenedioxythiophene polystyrene sulfonate (PEDOT:PSS), is sensitive to humidity and thus affects the stability of the PSCs. Herein, we employ a small molecule, 4, 4′, 4′′‐tris( N ‐3‐methylphenyl‐ N ‐phenylamino) triphenylamine ( m ‐MTDATA) to replace PEDOT:PSS as a new HTM for inverted PSCs. Compared to a PEDOT:PSS‐based device, m ‐MTDATA‐based PSCs exhibit enhanced performance. The highest power conversion efficiency (PCE) was notably improved from 13.44 % (PEDOT:PSS) to 18.12 % ( m ‐MTDATA), suggesting that m ‐MTDATA could be an efficient HTM to achieve high performance inverted PSCs. Furthermore, the m ‐MTDATA‐based device demonstrated improved stability (retaining 90 % PCE) under ambient conditions over 1000 h compared with the PEDOT:PSS‐based devices (retaining 40 % PCE). Abstract : Small molecule, big results : Inverted perovskite solar cells were fabricated using 4, 4′, 4′′‐tris( N ‐3‐methylphenyl‐ N ‐phenylamino) triphenylamine ( m ‐MTDATA) as a small‐molecule‐based hole‐transporting material (HTM). High efficiency (i.e., 18.12 %) and improved stability (i.e., retaining 90 % PCE under ambient conditions for 1000 h) was obtained when compared with devices fabricated using PEDOT:PSS as the HTM (13.44 and 40 %, respectively).